Physics vlogs learning videos on parabolic motion on youtube channels based on scientific approach - Jaka Surya; Yani Suryani; Antomi Saregar (CV FOUNDAE, 2022)
Physics learning media that attract students' learning interests are difficult for physics teachers to find. This research aims to produce a physics vlog learning video on YouTube that is suitable for use, to find out the responses of teachers and students regarding the developed learning media, and to find out the method of video development. The research method used was Research and Development with the Borg and Gall model. The feasibility of the learning video was obtained from the assessment by six material, media, and IT validators. Two validators represented each validation. The validation results showed that the learning video was feasible. The media, material, and IT experts validated the product with a percentage of 84, 72.25, and 98, respectively. The teachers and students were satisfied with the learning video, as proven by the percentages of 85 for the small-group trial, 94 for teachers field testing, and 78 for the large-scale trial. The results declared that the product was feasible to use. Thus, the developed physics learning video can be implemented in the learning process as a learning medium.